Is the taint argument real? Public perceptions of juries that include felon-jurors - Binnall, James Michael (Psychology, crime & law, 2024)
In forty-nine states, the federal system, and the District of Columbia, individuals with a felony conviction are statutorily restricted from serving as jurors. Proponents of felon-juror exclusion justify the practice by suggesting that those with a felony criminal history lack character, and if allowed to serve, would ‘taint’ the appearance of the jury system. This study assesses that claim by measuring the public’s opinion of juries that include a juror with a felony criminal history. Using a two-by-two vignette design and drawing on a sample of 200 participants, we vary two experimental factors: the presence of a felon-juror on the jury and the verdict rendered by the jury (guilty/not guilty). Results show that participants’ views of ‘illicit’ juries do not differ statistically from homogeneous juries without a felon-juror, for either verdict condition, undermining the ‘taint’ argument. Results also suggest that under certain conditions, the inclusion of a felon-juror may bolster views of the jury and resulting verdicts. Adding to a growing literature on felon-juror exclusion, these findings call into question the character rationale for felon-juror exclusion and suggest that diversity of experience in the form of a criminal history does not undermine the appearance of the jury.